Relationship between Alpha-toxin production and biofiJm for1nation by Staphylococcus aureus isolated from Eye's infections - Ismail, M. Cb. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Staphylococcus aureus is a common pathogen associated  with eyeÂ·sinfections.  S. aureus is capable of biofilm fonnation, which increases its persistence and boots its levels of antimicrobial resistance . A total of 50• aureus isolated from eyes f patientwith eye's infection : 41( 82%)isolates  were positive - alpha tox in production and 37 (74 %)  isolates were  posilive  - biofilm formation .Where as  32 (64%)    isolates were positive - alpha toxin production .and biotilm formation, 11 (22%) Lsolatcs were negative- alpha toxin production and biofilm formation and 7(14%) isolates  were showed  different  production. Rcsulets showed, high sigoificant association between alpha toxin productiÂ·on and biofilm formation inS. aureus isolates.